Faktor-Faktor yang Mempengaruhi Keputusan Pembelian melalui Aplikasi Shopee pada Generasi Z - Golda Chrissty Natalie; Amelia Setiawan; Hamfri Djajadikerta (GEMILANG: Jurnal Manajemen dan Akuntansi, 2025)
The rapid development of e-commerce has encouraged digital companies such as Shopee to implement various promotional strategies, such as discounts, free postage vouchers, and variations of outlets, in order to attract consumer buying interest, especially from the Z generation. This study aims to analyze the influence of each of these strategies on the interests and purchasing decisions through the Shopee application, as well as studying the effectiveness of the strategy from the management accounting point of view. Using a quantitative approach with the PLS-SEM method on 102 generation Z respondents, the results showed that only free postage vouchers had a significant effect on purchase interest, while discounts and outlet variations did not show significant effects. This finding becomes an important foundation for management accounting in conducting cost-hanefit analysis-based evaluations: Statistically ineffective promotional strategies can cause a waste of company resources. Therefore, this information can be used by management to assess the efficiency of promotional costs, prepare a more targeted marketing budget, and direct resources to incentives that are proven to have a positive impact on consumer behavior. Thus, this study contributes to providing empirical data that can support managerial decision making based on efficiency and economic value.